Constitutional legitimacy - the principle of the presumption of innocence for the accused in the Code of Criminal Procedure (The International Journal for Scientific Research, 2026)
The legal system, as a set of rules governing individual conduct, is the responsibility of the state to impose penalties and punishments on those who violate these rules. This is done to preserve the integrity, security, and stability of society, guarantee public interests, and protect individual freedoms. The penal code focuses on addressing all matters necessary for the proper functioning of social life, ensuring rights and freedoms, and preventing any individual from infringing upon those rights. However, the accused has the right to defend themselves. Criminal law does not permit the deprivation of the accused's freedom and rights, and it also protects the public interest. The principle of the presumption of innocence in criminal law is a fundamental guarantee of procedural legality. The importance of this principle is evident when taking criminal actions that affect personal freedom and when managing criminal evidence. It is a legal safeguard that the legislator must consider when defining criminal procedures to prevent the infringement of rights and freedoms. Due to its strong connection to personal freedom, this principle covers all stages of criminal proceedings, leading to outcomes that benefit the accused.
Keywords: Legality; Innocence; Accused; Criminal Procedures; Presumption of Innocence